IMPLEMENTASI PEMBELAJARAN “INQUIRY SMALL RESEARCH” UNTUK MENINGKATKAN SIKAP ILMIAH DAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN BIOLOGI - Wachidatul Linda Yuhanna; Raras Setyo Retno; Juwanita Juwanita (Bioilmi: Jurnal Pendidikan, 2017)
This research aims to implement Inquiry Small Research to improve the scientific attitude and achievement of students in vertebrate zoology This research was conducted in second semester with 38 students. This classroom action research is conducted in 2 cycles, each cycle through planning, action, observation and reflection. Data collection using observation sheet to know the scientific attitude and cognitive test to measure student achievement. The results showed that implementation of Inquiry Small Research for scientific attitude of students with good and excellent category experienced an increase from pre-cycle and cycle I by 54%, and from cycle I and II increased by 6%. Thus, overall from the pre-cycle stage to cycle II, students' scientific attitudes increased by 60%. The increase of student achievement by 27%, from pre cycle and cycle I, from cycle I and cycle II experienced 39% improvement. Thus, overall from pre-cycle stage to cycle II, student achievement has increased by 66%. The conclusion of this research is through implementation of Inquiry Small Research can improve scientific attitude and student achievement.